Treatment for Retinopathy of Prematurity in an Infant with Adenoviral Conjunctivitis - Murat Gunay; Gokhan Celik; Rahim Con (Hindawi Limited, 2015)
Retinopathy of prematurity (ROP) has been a major problematic disorder during childhood. Laser photocoagulation (LPC) has been proven to be effective in most of the ROP cases. Adenoviral conjunctivitis (AVC) is responsible for epidemics among adult and pediatric population. It has also been reported to be a cause of outbreaks in neonatal intensive care units (NICU) several times. We herein demonstrate a case with AVC who underwent LPC for ROP. And we discuss the treatment methodology in such cases.